THE DEGREE OF POSSESSING STRATEGIC PLANNING SKILLS AMONG ACADEMIC LEADERSHIPS IN JORDANIAN UNIVERSITIES - Al Rawashdi, Firas Muhammad; Alnawaiseh, Musa Abedel Latif Ibrahim; Basioni, Eman Sabri; Alnawaiseh, Mahmoud Barakat (European Scientific Journal, ESJ, 2014)
The aim of this study is to identify the degree of possessing strategic planning skills by academic leaders in Jordanian university. Strategic planning is not just a guarantee for an organization to sustain its financial position or supplying it with the ability to sustain its reserves, but it is a systematic process that involves several stages and steps through which the current position of the organization analyzes their strengths and weaknesses, the opportunities and threats they encounters, identifies its vision and aims, chooses the strategic alternatives to achieve the objective effectively within the surrounding environmental conditions, and setting the strategic general plan as well as the strategies related to different functional areas. Other reasons includes preparing the cultural environment of the organization, preparing administrative leaders and improving communications and giving out information which is necessary for making better decisions, and setting executive plans and schedules as well as monitoring, follow-up and evaluating the performance of the organization (Farrah et al. 2001). Hussy (Hussy, 1982, p3) suggested that strategic planning is "an essential part of management, and a vital element because it shows the awareness of the future, and prepares the requirements in dealing with it".